Self-Efficacy as a Predictor of Resilience in Adolescents: Insights from a Systematic Literature Review - Ghazal Moin; Ameer Muhammad; Noor ul Huda Zeeshan (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: As an internal factor, self-efficacy is expected to influence the level of mental resilience in adolescents, particularly in managing the stress and pressure they face in academic and social environments. Objective: This study aims to provide deeper insight into the role of self-efficacy in supporting resilience in adolescents. Method: This study uses the Systematic Literature Review method by collecting 12 references from studies published between 2017 and 2023. The review process was conducted using a meta-synthesis approach, which allowed researchers to identify, assess, and interpret findings from various studies relevant to the research topic to answer the questions set beforehand. Result: The results of the literature analysis show a positive correlation between self-efficacy and resilience in adolescents. Adolescents with high levels of self-efficacy tend to have better abilities in facing academic, social, and emotional challenges. This study also reveals that self-efficacy plays an important role in increasing mental resilience and helping adolescents more effectively overcome their problems. Conclusion: Self-efficacy plays a significant role in shaping resilience in adolescents. Adolescents with high confidence in their abilities can better cope with difficulties and persevere in stressful situations. Contribution: This study contributes to enriching the understanding of the role of self-efficacy as a factor that supports resilience in adolescents.